CURRICULUM MODEL FOR BOARDING SCHOOL MEMORIZATION OF THE QURAN WITH STRENGTHENING UNDERSTANDING OF THE CONTENT OF THE VERSES - Hakim, Abdul; Rosyada, Dede; Syahrullah, Syahrullah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
The reality is that some tahfizh institutions still emphasize the quantitative aspect of memorization, while understanding the meaning and content of the verses of the Qur'an has not been systematically integrated into the learning curriculum. In fact, strengthening the understanding of the content of the verses is an important element in forming students who not only memorize the textual, but are also able to internalize the values ​​of the Qur'an in their attitudes, behavior, and social life. This study uses a qualitative approach with the Design and Development Research (DDR) method, which is specifically aimed at developing a relevant and contextual curriculum model in educational institutions of tahfizh Al-Qur'an. The results of the study indicate that the curriculum model of tahfizh Al-Qur'an at the Ibnu Jauzi Islamic Boarding School in Bogor was developed in an integrative manner by combining memorization programs (tahfizh), understanding the meaning of verses (fahm al-ayat), and strengthening the applicable values ​​of the Qur'an. Strengthening understanding of the verse's content is carried out through simple thematic interpretation learning, mufradat studies, asbabun nuzul, and discussions of moral and social values ​​contained in the memorized verses. This research is expected to provide theoretical and practical contributions to the development of a more holistic curriculum model for Islamic boarding schools for memorizing the Qur'an, as well as serving as a reference for Islamic educational institutions in integrating Qur'an memorization with continuous strengthening of understanding of verse content.